Implementation of android apps in MSME digital transactions - Syahrial, Riza; Sari, Jamah; Nasri, Jelman; Trilaksono, Agustinus Rio; Hiswara, Indra (SEAN Institute, 2024)
The objective of this study is to ascertain the challenges encountered by micro, small, and medium enterprises (MSMEs) in traditional transaction processes and to determine how Android application technology can serve as a novel remedy to these challenges. In this context, the need for consumers and MSME participants to conduct transactions quickly, securely, and easily is of the utmost importance. As a result, the functionality testing and prototyping of Android applications for MSME digital transactions constitute a crucial stage in assisting the growth of MSMEs in the digital age. The method of prototyping is an efficient strategy for the development of Android applications for MSMEs. Interface implementation and the system design phase of the Android application for MSME digital transactions have also been completed utilising the UML (Unified Modelling Language) modelling method. System testing employs seven test scenarios and the blackbox testing method; the outcomes demonstrate that every feature is operational in accordance with the system's functionality. Supporting the growth of micro, small, and medium-sized enterprises (MSMEs) in the digital age requires the development of Android applications for MSME digital transactions via prototyping and functionality testing, according to the findings of this study. It is anticipated that by facilitating digital transactions for MSMEs, this application will boost the development and competitiveness of MSMEs.